Maximising the potential for bacterial phenotyping using time‐of‐flight secondary ion mass spectrometry with multivariate analysis and Tandem Mass Spectrometry. (21st March 2014) - Wehrli, Patrick M.; Lindberg, Erika; Angerer, Tina B.; Wold, Agnes E.; Gottfries, Johan; Fletcher, John S.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; et al.
<x xml:space="preserve">Abstract</x> The increasing trend towards bacteria becoming resistant to current antibiotic treatments is of great concern to the healthcare industry with severe potential consequences for society as a whole. In many cases, it is the interaction of the antibacterial agent with the targets within the bacterial envelope of the microorganism that is a critical factor. Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) is uniquely capable of probing the chemistry in this region. This study aimed at optimising sample preparation and data pre‐processing for bacterial analysis with ToF‐SIMS and principal components analysis to study small chemical differences related to changes in bacterial phenotype that will help to find new antibiotics and understand how antibiotics are trafficked in the bacteria. ToF‐SIMS analysis was performed using a J105 instrument equipped with a 40 kV C60+ ion source. Combination of positive and negative ion mode data enhanced the multivariate model quality regarding classification and aided chemical identification particularly when coupled with tandem mass spectrometry. Copyright © 2014 John Wiley & Sons, Ltd.